Pengaruh Aplikasi M-Pajak, Sosialisasi Perpajakan, dan Tax Complience Cost terhadap Kepatuhan Wajib Pajak UMKM Orang Pribadi yang Terdaftar di KPP Pratama Singaraja - Bagus Palguna I Gusti; Eka Dianita Marvilianti Dewi Putu (Vokasi : Jurnal Riset Akuntansi, 2023)
This research aims to know the influence of the M-Pajak application as a Modernization of the Tax Administration System, Tax Socialization, and Tax Compliance on the Compliance Level of MSME Taxpayers (Wajib Pajak UMKM) who are registered and actively fulfill their tax obligations at Kantor Pelayanan Pajak (KPP) Pratama Singaraja. This research is classified as quantitative research with a total of 128 individual taxpayers who are registered at KPP Pratama Singaraja. The sampling technique in this research used a purposive sampling method. The data used are primary data using distributed questionnaires. Collected data processed by IBM SPSS version 24 software. Partial testing shows that all the independent variables in this study have a positive effect on Taxpayer Compliance.